A Systematic Review of Advanced Imaging Modalities for Bladder Cancer: Comparative Analysis of Strengths and Limitations - Saba Maqsood; Muhammad Omair Siddique; Aftab Ahmed; Saba Akram; Hassan Raza Asghar; Pakeeza Shafiq; Muhammad Arsalan Shah (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Bladder cancer was seen to be amongst the most common urological malignancies, which required very sensitive approaches of detection that were also reliable for grading to improve patient outcomes. Diagnostic potential of various imaging modalities such as Multiparametric MRI (mpMRI), Contrast-Enhanced Ultrasound (CEUS), Blue Light Cystoscopy (BLC), Confocal Laser Endomicroscopy (CLE), Positron Emission Tomography (PET), Narrow Band Imaging (NBI) and Optical Coherence Tomography (OCT) were explored. This systematic review assessed the effectiveness of these imaging modalities to detect and stage bladder cancer to improve treatment outcomes and patient satisfaction.